Original paperThe effect of central shielding in the dose reporting for cervical cancer in EQD2 era - Tharavichitkul, Ekkasit; Wanwilairat, Somsak; Watcharawipha, Anirut; Tippanya, Damrongsak; Jayasvasti, Rungtip; Chakrabandhu, Somvilai; Klunklin, Pitchayaponne; Onchan, Wimrak; Galalae, Razvan; Chitapanarux, Imjai (Journal of Contemporary Brachytherapy, 2013)
Purpose : To evaluate the cumulative dose at point A for three and four centimeters central shielding. Material and methods: The plans of external beam radiotherapy plus conventional intracavitary brachytherapy were performed. Three or four centimeters central shieldings (after 44 Gy) were applied to the standard whole pelvis irradiation. Additional intracavitary brachytherapy 4 × 7 Gy at point A was prescribed, and the cumulative dose in EQD2 (/ = 10) of 3 cm and 4 cm central shielding were evaluated. Results: The cumulative dose at point A in EQD2 (/ = 10) of 3 cm central shielding were 95.7 Gy for AR and 95.5 Gy for AL, while the cumulative dose at point As in EQD2 (/ = 10) of 4 cm central shielding were 90.8 Gy for AR and 91.2 Gy for AL. Conclusions : The 3 cm central shielding caused higher cumulative dose (in terms of EQD2 [/ = 10]) than 4 cm central shielding.